SUPPLY CHAIN NETWORK DESIGN OPTIMIZATION ACCOMMODATING DEMAND GROWTH FOR E-GROCERY - Dini Putri Prady, Amalia
PT X is a prominent e-grocery operating in Greater Jakarta Area. It offers 5,000 unique SKUs, which are vegetables, fruits, frozen goods, and dry goods. To serve their customers, PT X has three business services, which are Next Day (ND) delivery, Instant Delivery (ID), and business-to-business (B2B) services. The orders for all business services reach a total of 190 thousand orders per month. Each of this business services have their own characteristics of order profile and production processes. To thrive as a company, PT X need to maintain business’ economies of scale and keeping supply chain costs at minimum. It aims to minimize the total strategic supply chain costs for the next years. To do so, PT X needs to determine the best supply chain network design accommodating demand growth, which covers facility location, facility capacity, and service configuration. It covers the mid-mile to last-mile supply chain segment, which covers main fulfilment centres (MFCs), distribution hubs, and customers. This study solves the problem using operations research methodology. A mathematical model of supply chain network design is developed. The model is deterministic, multi-product, multi-period, and multi-echelon mixed integer linear programming (MILP) model. CPLEX solver, using Python API, is used to build and optimize model. The benefits of this study are (1) proposed optimal solution for supply chain network design problem of PT X and (2) a working computer-based mathematical model as tools of the given problem. Through optimization, this study concludes the optimal location, capacity, and service configuration for year 2023 to 2025, with total costs of Rp228,540,911,024.29. Further analysis is also conducted, such as sensitivity analysis, managerial implications, and guideline to use the tools generated by this study.